Cancer Immunotherapy Based on Natural Killer Cells: Current Progress and New Opportunities - Hu, Weilei; Wang, Guosheng; Huang, Dongsheng; Sui, Meihua; Xu, Yibing (Frontiers in Immunology, 2019)
Cancer immunotherapy has been firmly established as a new milestone for cancer therapy, with the development of multiple immune cells as therapeutic tools. Natural killer (NK) cells are innate immune cells endowed with potent cytolytic activity against tumors, and meanwhile act as regulatory cells for the immune system. The efficacy of NK cell-mediated immunotherapy can be enhanced by immune stimulants such as cytokines and antibodies, and adoptive transfer of activated NK cells expanded ex vivo. In addition, NK cells can arm themselves with chimeric antigen receptors (CARs), which may greatly enhance their anti-tumor activity. Most recently, extracellular vesicles (EVs) derived from NK cells show promising anti-tumor effects in preclinical studies. Herein, we carefully review the current progress in these NK cell-based immunotherapeutic strategies (NK cells combined with stimulants, adoptive transfer of NK cells, CAR-NK cells, and NK EVs) for the treatment of cancers, and discussed the challenges and opportunities for opening a new horizon for cancer immunotherapy.